2015
DOI: 10.1534/genetics.114.173856
|View full text |Cite
|
Sign up to set email alerts
|

Replisome Function During Replicative Stress Is Modulated by Histone H3 Lysine 56 Acetylation Through Ctf4

Abstract: Histone H3 lysine 56 acetylation in Saccharomyces cerevisiae is required for the maintenance of genome stability under normal conditions and upon DNA replication stress. Here we show that in the absence of H3 lysine 56 acetylation replisome components become deleterious when replication forks collapse at natural replication block sites. This lethality is not a direct consequence of chromatin assembly defects during replication fork progression. Rather, our genetic analyses suggest that in the presence of repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 118 publications
(211 reference statements)
0
28
0
Order By: Relevance
“…In S . cerevisiae , it has been shown that Mcl1 homologue Ctf4 is a major target of H3K56ac pathway 44 . Our data showed that Mcl1 expression could suppress hst4 Δ mutant phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…In S . cerevisiae , it has been shown that Mcl1 homologue Ctf4 is a major target of H3K56ac pathway 44 . Our data showed that Mcl1 expression could suppress hst4 Δ mutant phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…We next examined how the Rtt101 Mms22 E3 ligase is recruited to active replisomes. Ctf4 was an intriguing candidate as it was previously found to interact with Mms22 [ 3 , 18 , 36 ]. Indeed, genetic analysis revealed that the growth defect of ctf4Δ cells on genotoxic drugs was epistatic with RTT101 and even slightly suppressed the sensitivity of mms22Δ cells ( Fig 3A ), consistent with previous findings [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the replication fork progression defect is enhanced in mrc1Δ compared to tof1Δ and csm3Δ mutants [ 1 ], implying that Mrc1 also promotes replication functions independent of Tof1 and Csm3. Ctf4, the yeast homologue of human AND1, bridges the interaction of the primase, DNA polymerase-α, to the CMG helicase [ 3 , 5 , 18 ]. Although the coupling of the CMG to leading and lagging strand DNA polymerases preserves genome integrity during unperturbed DNA replication, this mechanism is partially disrupted when forks encounter replication stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of replication fork dynamics in living cells also suggests that the sites of DNA synthesis are sites of decondensed chromatin 4 . Posttranslational modification of histones, such as acetylation of histones H3 and H4, has been reported to regulate DNA replication 5 6 7 probably by affecting chromatin structures 8 . However, the molecular mechanisms underlying the DNA replication-associated alteration of chromatin structures remain unknown.…”
mentioning
confidence: 99%